KONTRIBUSI SISTEM PENGARSIPAN DAN LAYANAN SATU ATAP TERHADAP EFISIENSI KERJA DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN LAMONGAN - PAMUJI LESTARI, TRI (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT   Filing system is one of the supporting of the smooth working employees. Low filing system caused employee work efficiency is not achieved properly, because there are other factors that affect the filing system. One-stop service that complex and convolute, expensive tariff, and a long processing time has decreased work efficiency. The problem in this research are 1) How does the condition filing system, one-stop service and work efficiency in the department of population and civil registration in region Lamongan. 2) How did the contribution of the filing system and one-stop service to the work efficiency the department of population and civil registration in region Lamongan. This type of research is descriptive research with quantitative research approaches. Sample and population of this research is all staff of internal employees totaling 27 employees. Instrument in this research using a questionnaire. Techniques of data analysis using multiple linear regression.The conclusion of this research are: (1) Condition filing system is high, one-stop service as very high, and the work efficiency in the Department of Population and Civil Registration in Region Lamongan is high.2) (a) filing system partially contributes  had a low affect  the work efficiency. (b) one-stop service are contributes moderate way to the work efficiency. (c) filing system, and one-stop service are simultanly contributes to work efficiency in a moderate way.   Keywords: Filing Systems, One-Stop Services, Work Efficiency